Claterization of Primary Schools In The Surakarta Region Using The K-Medoids Method Based on School Costs and Facilities - Rokhmah, Siti (Institut Teknologi Bisnis AAS Indonesia, 2023)
Basic education has an important role in forming the foundation of a child's character. The city of Surakarta is a city that has many choices of elementary schools, both public and private. The large number of elementary schools requires clustering, so that it can help the government and the community in decision making. The most important factors in choosing an elementary school are school facilities and costs, so the clustering in this research is based on educational costs and the facilities provided by the school. The method used in this research is the K-Medoids clustering method, namely a clustering method that groups data based on groups that have maximum similarity. To evaluate the clustering results, silhoette value calculations are used. It is hoped that this research can help the government, especially the education department, in mapping elementary schools in the Surakarta area and assist parents in determining elementary school choices.